Estimation of Intake of Critical Nutrients Associated with Noncommunicable Diseases According to the PAHO/WHO Criteria in the Diet of School-Age Children in Montevideo, Uruguay (2022)
ABSTRACT: Purpose: To estimate the effect of the consumption of products with an excessive amount of critical nutrients associated with NCDs, according to the PAHO Nutrient Profile Model on the quality of the diet of Uruguayan school-age children (4 to 12 years). Methods: A 24 h recall of food intake was conducted in a representative sample of 332 participants in the evaluation of the School Feeding Program in 2018 in public schools in Montevideo, Uruguay. Food and preparations were categorized according to the NOVA food classification, according to the nature, extent, and purposes of the industrial processes they undergo. Later, they were analyzed according to the Pan American Health Organization Nutrient Profile Model (PAHO NPM) to identify processed and ultra-processed products with an excessive content of critical nutrients. Results: Only 0.52% of children consumed exclusively natural foods, or culinary ingredients. Twenty-five per cent of children consumed ≥4 products categorized with an excessive content of free sugars, total fat, or saturated fat according to the PAHO NPM; in the case of excessive sodium, this was 40%. In general, children who included products with excessive free sugars, sodium, or saturated fat in their diet exceeded the limits established by the World Health Organization, and, as a result, their diet is of poorer nutritional quality compared to children who did not consume such products. Conclusion: Diets free of ultra-processed and processed products with excess free sugars, total fats, saturated fats, and sodium increased the chances of school-age children in Montevideo of meeting WHO nutrient intake recommendations. Meanwhile, intake of each additional gram of products with excessive critical nutrients according to PAHO NPM, significantly worsens diets, preventing children from meeting WHO recommendations. Keywords: NOVA; nutrient profiling; food processing; ultra-processed food; school-age food intake